Kurikulum Merdeka: Transformasi Pembelajaran yang Relevan, Sederhana, dan Fleksibel - Prisca Regina Putri Novia Rani; Maduki Asbari; Vincensius Dandi Ananta; Ilham Alim (AGUSPATI RESEARCH INSTITUTA, 2023)
The purpose of this study is to support the development of students' potential through the Independent Curriculum which is designed so that the learning system becomes more relevant, simple, and flexible by following the changing times. In this study report using a descriptive qualitative method by taking notes because the source of the data obtained by listening to oral narration from the BSKAP Youtube channel of the Ministry of Education and Culture entitled